Experiences of cervical screening and barriers to participation in the context of an organised programme: a systematic review and thematic synthesis. Issue 2 (12th April 2016) - Chorley, Amanda J.; Marlow, Laura A. V.; Forster, Alice S.; Haddrell, Jessica B.; Waller, Jo
Abstract: Objective: As uptake of cervical screening continues to decline, this systematic review synthesises the qualitative literature on women's perceptions and experiences of cervical screening in the context of an organised call–recall programme, in order to understand the barriers to informed uptake. Methods: We searched nine databases for English language peer‐reviewed publications reporting on qualitative data from screening‐eligible women, exploring barriers to cervical screening in countries that offer a nationally organised call–recall programme. Evidence was integrated using thematic synthesis. Results: Thirty‐nine papers from the UK, Australia, Sweden and Korea were included. The majority of participants had attended screening at least once. Two broad themes were identified: (a) should I go for screening? and (b) screening is a big deal. In considering whether to attend, women discussed the personal relevance and value of screening. Women who had previously attended described how it was a big deal, physically and emotionally, and the varied threats that screening presents. Practical barriers affected whether women translated screening intentions into action. Conclusions: The variation in women's understanding and perceptions of cervical screening suggests that interventions tailored to decisional stage may be of value in increasing engagement with the invitation and uptake of screening in those who wish to take part. There is also a need for further research with women who have never attended screening, especially those who remain unaware or unengaged, as their perspectives are lacking in the existing literature. © 2016 The Authors. Psycho‐Oncology Published by John Wiley & Sons Ltd.